2010
DOI: 10.1016/j.bpj.2009.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Nanogap Dielectric Spectroscopy for Aptamer-Based Protein Detection

Abstract: Among the various label-free methods for monitoring biomolecular interactions, capacitive sensors stand out due to their simple instrumentation and compatibility with multiplex formats. However, electrode polarization due to ion gradient formation and noise from solution conductance limited early dielectric spectroscopic measurements to high frequencies only, which in turn limited their sensitivity to biomolecular interactions, as the applied excitation signals were too fast for the charged macromolecules to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…1b). In contrast with the parallel electrode architecture described in the literature2122, which measures the direct (as opposed to fringing) capacitance, the planar electrodes used in this work, take advantage of the fringing field capacitance in the solution (see Supplementary Note online). The sensing electrode was connected to the surrounding circuits.…”
Section: Resultsmentioning
confidence: 99%
“…1b). In contrast with the parallel electrode architecture described in the literature2122, which measures the direct (as opposed to fringing) capacitance, the planar electrodes used in this work, take advantage of the fringing field capacitance in the solution (see Supplementary Note online). The sensing electrode was connected to the surrounding circuits.…”
Section: Resultsmentioning
confidence: 99%
“…It is well reported that the low-frequency dielectric response is dominated by the ionic relaxation of the buffer [32,41,42,43], complicating detection. The complex composition of the PBS buffer (0.01 M phosphate buffer, 2.7 mM KCl, 0.137 M NaCl) may be the source of this behaviour.…”
Section: Dielectric Spectroscopy Sensing Of Dnamentioning
confidence: 99%
“…These sensors are now widely applied in detections of various scales, e.g. DNA [21][22][23] , proteins 24,25 , cells 26,27 and bacteria 28 . For impedance-based measurements, an electrode-electrolyte double layer will be formed at the electrode surface, and this double layer capacitance behaves as a parasitic component to reduce the sensitivity 29 .…”
Section: Introductionmentioning
confidence: 99%